Generation of islet-like cell aggregates from human non-pancreatic cancer cell lines - Kanafi, M.; Mamidi, M.; Sureshbabu, S.; Shahani, P.; Bhawna, C.; Warrier, Sudha; Bhonde, R. (Kluwer Academic Publishers, 2014)
To explore a novel source for the derivation of islets, we examined the differentiation potential of human non-pancreatic cancer cell lines, HeLa (cervical carcinoma cell line) and MCF-7 (breast cancer cell line). These cells were subjected to a serum-free, three-step sequential differentiation protocol which gave two distinct cell populations: single cells and cellular aggregates. Subsequent analysis confirmed their identity as pancreatic acinar cells and islet-like cell aggregates (ICAs), as evidenced by amylase secretion and diphenylthiocarbazone staining respectively. Reverse transcriptase-PCR and immunocytochemistry assessment of the ICAs revealed the expression of pancreatic specific markers Ngn-3, Glut-2, Pax-6 and Isl-1. These ICAs secreted insulin in response to glucose challenge, confirming their functionality. We propose that ICAs generated from HeLa and MCF-7 cell lines could form a promising in vitro platform of human islet equivalents (hIEQs) for diabetes research.